2018
DOI: 10.1016/j.jaerosci.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pathogens were detected from human exhaled breath using a novel protocol

Abstract: A B S T R A C TIt is generally believed that influenza outbreak is associated with breath-borne transmission of viruses, however relevant evidence is little for that of respiratory bacterial infections. On another front, point-of-care infection diagnostic methods at the bedside are significantly lacking. Here, we used a newly developed protocol of integrating an exhaled breath condensate (EBC) collection device (PKU BioScreen) and Loop Mediated Isothermal Amplification (LAMP) to investigate what bacterial path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 50 publications
0
34
0
2
Order By: Relevance
“…With respect to bioaerosol emissions, Zheng, Chen, Yao, and Li (2018) utilized a new protocol (combing exhaled breath collection with Loop Mediated Isothermal Amplification (LAMP) and detected Haemophilus influenzae, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Methicillin-resistant Stphylococcus aureus (MRSA) in exhaled breath. Among these pathogens, H. influenzae was found to be the leading cause for the respiratory bacterial infections .…”
Section: Bioaerosol Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…With respect to bioaerosol emissions, Zheng, Chen, Yao, and Li (2018) utilized a new protocol (combing exhaled breath collection with Loop Mediated Isothermal Amplification (LAMP) and detected Haemophilus influenzae, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Methicillin-resistant Stphylococcus aureus (MRSA) in exhaled breath. Among these pathogens, H. influenzae was found to be the leading cause for the respiratory bacterial infections .…”
Section: Bioaerosol Special Issuementioning
confidence: 99%
“…They have indicated that children presented the highest exposure risk of airborne endotoxin. In addition to traditional detection methods, some studies in this special issue reported the developments of new bioaerosol detection methods such as use of LAMP together with microfluidics and DNA stain together with UV-APS (fluorescence-based bioaerosols sensor) Nasrabadi, An, Kwon, & Hwang, 2018;Zheng et al, 2018). Liu, Zhang, Wen, and Wang (2018) reported a bioaerosol detection system that combines sampling, transport, DNA extraction and also LAMP-based detection, while Nasrabadi et al (2018) reported a new method of differentiating alive and dead bioaerosol particles using fluorescence-based method.…”
Section: Bioaerosol Special Issuementioning
confidence: 99%
“…此外, 这种不平衡的状 态也会引起细菌病原体的过度繁殖或者新的病原体 入侵, 造成呼吸道入侵式感染. 研究指出, 对于细菌 呼吸系统感染的病例, 大部分是由流感嗜血杆菌造 成, 而且一些耐药细菌如耐甲基西林金黄色葡萄球 菌(MRSA)可以通过呼出气释放在环境中 [89] , 儿童哮 喘的发生与莫拉菌属呈正相关 [90] . 由气溶胶传播导 致的呼吸系统感染仍然是危害人类生命的一大杀手,…”
Section: 当呼吸道中的菌群结构平衡一旦被打破 某种优势unclassified
“…用来做疾病的早期检测 [141,142] , 也有研究利用空气中 人体脱落的细胞DNA来做医学指纹鉴定 [143,144] . 在呼 出气采集装置方面, 也取得了一定的进展, 比如北京 大学研发的BioScreen呼出气采集装置, 能够在几分 钟内采集200~300 μL呼出气冷凝液 [89,145] . [146,147] , 低温等离 子体和静电场具有良好的研究应用前景.…”
Section: 近年来 呼出气中的生物成分如生物标志物日益被unclassified
“…Environmental microbial analysis methodology is needed, not only for health risk assessment and manufacturing management, but also for a better understanding of the environment and ecosystem in order to identify the source, and transmission behaviour of microbes (Anderson et al ; Li et al ; Traversi et al ). Human activities also pose high potential health risks to people in hospitals, poultry markets and schools through pathogenic microbes, for example the influenza virus (Brągoszewska et al ; Wei et al ; Zheng et al ). Allergies can be caused by airborne fungi and mushrooms, some of which could be spread by air conditioning systems.…”
Section: Introductionmentioning
confidence: 99%